Optimizing Whole Brain Radiotherapy Treatment and Dose for Patients With Brain Metastases From Small Cell Lung Cancer - Li, Hanming; Li, Wang; Qi, Chao; Zhou, Lu; Wen, Fengyun; Qu, Yanli; Yu, Hong (Frontiers in Oncology, 2021)
Purpose This study aimed to evaluate the survival outcomes of whole brain radiotherapy (WBRT) compared to whole brain radiotherapy plus local radiation boost (WBRT + boost), and further identify whether higher biologically effective dose (BED) of WBRT + boost translates into a survival benefit in small cell lung cancer (SCLC) patients with brain metastasis (BM). Methods SCLC patients with BM from January 1, 2012, to December 31, 2019, were retrospectively analyzed. Overall survival (OS) and intracranial progression-free survival (iPFS) were evaluated by the Kaplan–Meier method and compared by the log-rank test. Univariate and multivariate regression analyses of prognostic factors for OS were performed using Cox proportional hazards regression models. The cutoff value of BED was determined by the receiver operating characteristic (ROC) curve analysis. Results Among the 180 eligible patients, 82 received WBRT + boost and 98 received WBRT. Both OS and iPFS in the WBRT + boost group were significantly superior to those in the WBRT group (median OS: 20 vs. 14 months, p = 0.011; median iPFS: 16 vs. 10 months, p = 0.003). At a cutoff value of 58.35 Gy in the WBRT + boost group, 52 for the high-BED (>58.35 Gy) group, 30 for the low-BED (≤58.35 Gy) group. High BED was significantly associated with improved OS and iPFS compared with low BED in the WBRT + boost group (median OS: 23 vs. 17 months, p = 0.002; median iPFS: 17 vs. 10 months, p = 0.002). Conclusions Compared with WBRT alone, WBRT + boost improved OS and iPFS in SCLC patients with BM. High BED (>58.35 Gy) for WBRT + boost may be a reasonable consideration for SCLC patients with BM.